Molecular imaging of tumor metabolism and apoptosis - Haberkorn, Uwe; Markert, A.; Mier, Walter; Askoxylakis, V.; Altmann, Annette (Oncogene, 2011)
Increased metabolism in a number of cellular pathways is a common feature of malignant tumors. This metabolic hallmark of neoplastic tissue led to the development of radiopharmaceuticals for the assessment of transport and enzymatic activity for tumor diagnosis and staging. The malignant transformation causes the activation of oncogenic proteins and signaling pathways that stimulate glycolysis. The resulting high-glucose metabolism of cancer cells allows PET imaging using FDG. Other molecules frequently applied in preclinical and clinical studies are 11C-methionine, tyrosine analogs and choline-based tracers. Using quantitative procedures they enable therapy monitoring by assessment of changes in transport and metabolization. As apoptosis is an important mechanism of cell death in tumors responding to treatment, non-invasive assessment of apoptosis using tracers for detection of phosphatidyl-serine presentation and/or caspase activation could be used as a surrogate marker for therapeutic efficacy.
Gesehen am 25.07.2022